Socio-economic, environmental and health impacts of dietary transformation in Bangladesh: A scenario simulation study for the period 2022-2040 - van Dijk, Michiel; de Lange, Thijs (International Food Policy Research Institute, 2024)
Recently, in many low- and middle-income countries, a rise in income, urbanization and a change in lifestyles have resulted in a shift in dietary patterns from mainly staple crops, such as rice, wheat and maize, towards a diet characterized by higher intake of meat, sugar and processed foods. This so-called nutrition transition has led to a situation in many countries that is referred to as the double burden of malnutrition, which is defined as the simultaneous observation of both undernutrition and overweight, obesity, and diet-related non-communicable diseases. The change in diets, and in particular the worldwide rise in the consumption of animal protein, also has had a strong negative impact on the environment, including loss in biodiversity, water resource depletion, deforestation, and an increase in greenhouse gas (GHG) emissions.